THE IMPACT OF WORK DISCIPLINE AND WORK TRAINING ON EMPLOYEE PERFORMANCE AT THE SECRETARIAT OF THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL (DPRD) OF TANJUNGPINANG CITY, RIAU ISLANDS PROVINCE - Nasrul; Sri Wahyuningsih; Yeti Rohayati (STMIK Indonesia Banda Aceh, 2026)
This study aims to determine the influence of work discipline and work training on the performance of employees of the Tanjungpinang City DPRD Secretariat, Riau Islands Province. Work discipline is very important for the level of employee performance. The research method used in this study is a quantitative research method. The population of this study was 90 employees of the Tanjungpinang City DPRD, Riau Islands Province, while the sample in this study consisted of 90 employees of the Tanjungpinang City DPRD, Riau Islands Province. Based on the results of multiple linear regression tests, it can be concluded that work discipline and work training have an effect on the performance of employees of the Tanjungpinang City DPRD, Riau Islands Province of 65.1%, while the remaining 34.9% is influenced by other variables. The direction of the relationship between the two variables is positive, so it can be interpreted that the higher the work discipline, the higher the employee performance. Likewise, the higher the work training, the higher the employee performance